Multiplicity patterns of minimal zero sequences of Zp x Zp - Laylo, Vedes Ann Tagle (Animo Repository, 2013)
If G is a nite abelian group, let MZS(G k) denote the set of all minimal zero sequences of G with length k. In the class of groups G = Zp Zp, where p is an odd prime, this thesis discusses the structure of the elements in MZS(G k) with maximal length k, known as the Davenport constant. The multiplicity pattern of the minimal zero sequences of maximal length over Zp Zp are also determined. Furthermore, additional results which strengthen a known theorem about the multiplicity pattern of such sequences are presented.